Faktor Risiko Kejadian Stunting Pada Anak Balita Usia 24 – 59 Bulan di Wilayah Kerja Puskesmas Penyandingan Kabupaten OKU Tahun 2021 - Diana Estherina; Erma Gustina; Yusnilasari (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Stunting is still a problem in terms of nutrition and child development in Indonesia. Stunting in the province of South Sumatra in 20 18 amounted to 31.7 %. The prevalence of stunting in OKU Regency is 33.2%. The highest contributor to the stunting rate was the Pairing Health Center with 56 children under five. The purpose general of the research it is factor factors related to the incidence of stunting . This study is a correlation with case control design using secondary data from the MCH book and primary data through interviews. Variables examined included height toddler , the type of sex, the provision of breastfeeding , maternal education level, breastfeeding Eksklusif and birth weight. The number of samples in this study were 1 1 2 samples which included 56 case groups and 56 control groups. The sampling technique for the case group used a saturated sample and the probability sampling technique was used for the control group . The results showed that the variables related to the incidence of stunting were birth weight under five with p-value 0.073, giving MP-ASI p-value 0.342, exclusive breastfeeding p-value 0.095 and mother's education p-value 0.433. It is recommended to the puskesmas and related parties to increase the provision of information and socialization to the public about stunting and how to reduce the incidence of stunting in children under five.